Rapid flow cytometric method for viability determination of solventogenic clostridia - Linhová, Michaela; Branská, Barbora; Patáková, Petra; Lipovský, Jakub; Fribert, Petr; Rychtera, Mojmír; Melzoch, Karel (Folia microbiologica, 2012)
We endeavored to develop a method for viability determination of solventogenic clostridia and to apply it for monitoring acetone-butanol-ethanol (ABE) fermentation. Six fluorescent probes (propidium iodide [PI], ethidium bromide, fluorescein diacetate, carboxyfluorescein diacetate [cFDA], rhodamine 123, bis-(1,3-dibutylbarbituric acid)trimethine oxonol [BOX]) were tested in order to distinguish two subpopulations of live and dead clostridial cells in suspension. Three of them were found to be appropriate (PI, BOX and cFDA) for this purpose. Developed fluorescent staining methods were applied to batch fermentation processes of Clostridium pasteurianum and C. beijerinckii carried out in a laboratory bioreactor under anaerobic conditions. Whereas PI was found to be applicable to both strains, BOX was convenient only for viability determination of C. pasteurianum. Although cFDA can distinguish two cell subpopulations in suspension, it was found to be unsuitable for viability determination under tested conditions, since it reflected more variable esterase activity during sporulation cell cycle than viability. Flow cytometry in combination with convenient fluorescent probe has been proved to be a valuable tool for viability determination. We assume this rapid and simple method can help to obtain more complex and precise information about ABE fermentation.
Keywords: Clostridium; Fluorescent Dyes; mikrobiální viabilita; průtoková cytometrie; butanoly; ethanol; Acetone; Solvents; Staining and Labeling; Flow Cytometry; fermentace; barvení a značení; fluorescenční barviva; Butanols; Ethanol; rozpouštědla; Microbial Viability; Fermentation; aceton